Performance Evaluation of a Pelton Turbine with Fiberglass Composite Blades Using Three Nozzles in Different Positions - Nasruddin A. Abdullah; Syamsul Bahri Widodo; Suheri; Rita Syntia; Zainal Arif; Cut Inayah (JURUTERA - Jurnal Umum Teknik Terapan, 2024)
Renewable energy utilization has become a primary focus in addressing the negative impacts of fossil fuel usage for electricity needs. One proposed solution is using water flow energy through a Pelton turbine. However, traditional materials used in Pelton turbines, especially metals, have disadvantages such as high inertia and susceptibility to corrosion. In this study, we replaced the Pelton turbine's material with fiberglass composite, which offers lower inertia and better corrosion resistance. This study aims to evaluate the performance of the Pelton turbine using fiberglass composite material. Tests were conducted by connecting the turbine to a generator and installing three adjustable nozzles, divided into seven sections based on the number of nozzles opened. Voltage, current, and electric power were measured using a power meter. The results show that with a load consisting of LED light bulbs, the section with one nozzle open (Section 2) achieved the best power output of 1.11 watts, while the section with two nozzles open (Section 6) achieved the best power output of 1.66 watts. Without load, the highest voltage occurred in Section 2 with one nozzle open at 30.9 volts, while the highest power was recorded in Section 4 with two nozzles open at 31.26 volts